Legal Protection and Empowerment of Songket/Endek Fabric Weavers in Gelgel Village Tourism Area, Klungkung - Styawati, Ni Komang Arini; Mahendrawati, Ni Luh Made; Laksmi, Anak Agung Rai Sita; Wijaya, I Ketut Kasta Arya; Rideng, I Wayan; Widiati, Ida Ayu Putu; Mardika, I Made; Ekayani, Ni Nengah Seri; Wesna, Putu Ayu Sriasih; Utama, I Wayan Kartika Jaya; Muliana, I Wayan; Susanthi, I Gusti A.A. Dian; I Gusti Putu Ghosadhira Vedhastama; Erawati, Ni Putu Tina; Bongon, Miel S.; Villafuerte, Marcelo Roland C.; Vibandor, Demosthenes B. Vibandor; Sentelices, Leovigildo C.; Raymundo, Carlos M. (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Gelgel Village is one of the villages in Bali known for producing Balinese woven fabrics, namely songket and endek fabrics. Songket/endek fabric is one of the characteristics of Balinese cultural products. In order to preserve songket weaving, legal protection is necessary. Moving on from this matter, there are several problems experienced by participants in this program, namely: 1) Lack of interest of the younger generation in working as weavers, 2) Lack of compatibility of work results required by employers with weavers, and 3) Legal protection for workers and employers of songket/short cloth weaving in Gelgel Village, Klungkung. The activities carried out in this program were to provide counseling on the importance of preserving songket weaving as a cultural characteristic. These activities increased the younger generation's interest in weavers by counseling them on preserving songket weaving as a cultural characteristic. In addition, a good working relationship is needed in the songket/short woven fabric production process so that the weaving results are by the expectations of employers and consumers. Legal protection for weaving workers is to provide their rights as workers by applicable laws and regulations. Entrepreneurs are also encouraged to get legal protection by making Intellectual Property Rights (IPR) in the form of Copyright.